Pengaruh Kualitas Layanan Logistik terhadap Kepuasan Pelanggan dan Loyalitas Pelanggan pada Pengguna TikTok Shop di Indonesia - Lesmana, Nathanael Eugene; Rahayu, Siti; Trisnawati, Juliani Dyah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the effect of logistics service quality dimensions, including order accuracy, order condition, timeliness, and order discrepancy handling, on customer satisfaction and customer loyalty in TikTok Shop. A quantitative approach was employed by distributing questionnaires to 223 respondents. The data were analyzed using PLS-SEM with SmartPLS 4. The results show that all dimensions of logistics service quality have a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty. These findings highlight the importance of logistics service quality in enhancing customer experience and competitiveness in the e-commerce market. Keywords: Customer satisfaction; Customer loyalty; E-commerce; Logistics service quality; TikTok shop